Response of Financial Markets to COVID-19 Pandemic: A Review of Literature on Stock Markets - Bayu Arie Fianto; Masagus M. Ridhwan; Syed Alamdar Ali Shah; Muhammad Faris; Rafiatul Adlin Hj Mohd Ruslan (Emerging Science Journal, 2023)
The objective of this research is to consolidate the literature published on the COVID-19 crisis impact on global stock markets to gain managerial implications from the crisis. It performs a thematic bibliometric review of the literature published in Scopus-ranked journals since the beginning of the pandemic using FCWI, Piecharts, and VOSViewer. It identifies the most under-researched regions and eight emerging sub-themes. The research finds that the benchmark theme is market behavior during the COVID-19 crisis, whereas an emerging benchmark theme is the markets after the COVID-19 crisis. The holistic view of the literature supporting eight sub-themes suggests that the government's role is of utmost importance to handle the impact of the COVID-19 crisis, which should be industry-specific. It identifies that all eight sub-themes of the research are the future research directions in all and specifically in the South American, African, South East Asian, and Oceania regions till the crisis continues. Doi: 10.28991/ESJ-2023-SPER-03 Full Text: PDF